The other story [compact disc, unabridged] - Rosnay, Tatiana de, 1961- (Macmillan Audio, 2014)
When Nicholas was 24 years old, he stumbled upon a troubling secret about his family. In shock, he embarked on a journey to uncover the truth, but the answers wouldn't come easily. In the process of digging into his past, he began writing a novel that was met with phenomenal success, and was convinced he'd put his family's past behind him. But years later, Nicolas must reexamine everything he thought he knew, and learns that, however deeply buried, the secrets of the past always find a way out.